Effect of body mass index on inpatient rehabilitation outcome after stroke in a Southeast Asian cohort: a prospective study - Sze Chin Jong; Jovic Aguipo Fuentes; Angie En Qin Seow; Chien Joo Lim; Gobinathan Chandran; Karen Sui Geok Chua (Singapore Medical Journal)
Introduction: We examined the association between admission body mass index (BMI) and discharge rehabilitation functional outcome using the functional independence measure (FIM) in a Southeast Asian cohort of stroke patients during inpatient rehabilitation. Methods: A prospective, observational cohort study of stroke patients admitted to a single inpatient rehabilitation unit was conducted. Using the World Health Organization Asian standards, BMI was classified as underweight (<18.5 kg/m2), normal (18.5–22.9 kg/m2) and overweight (≥23 kg/m2). The primary outcome measure was discharge FIM, and secondary outcomes included FIM gain, FIM efficiency and FIM effectiveness. Results: Two hundred and forty-seven stroke subjects were enrolled. The mean age of the cohort was 59.48 (standard deviation [SD] 12.35) years; 64.4% (n = 159) were male and 52.6% (n = 130) had ischaemic stroke. The distributions of underweight, normal and overweight based on BMI on admission were 10.9% (n = 27), 33.2% (n = 82) and 55.9% (n = 138), respectively, and the distributions upon discharge were 11.7% (n = 29), 38.1% (n = 94) and 50.2% (n = 124), respectively. Significant small decreases in BMI from admission to discharge were found (median [interquartile range] 23.58 [23.40–24.70] vs. 23.12 [22.99–24.21]; P < 0.001). Similarly, clinically significant FIM gains (mean ΔFIM 26.71; 95% confidence interval 24.73, 28.69, P < 0.001) were noted after a median length of stay of 36 days. No significant relationships were found between BMI and discharge FIM (P = 0.600), FIM gain (P = 0.254), FIM efficiency (P = 0.412) or FIM effectiveness (P = 0.796). Conclusion: Findings from this study unequivocally support the benefits of acute inpatient stroke rehabilitation. Patients in the obese BMI range tended to normalise during rehabilitation. Body mass index, whether underweight, normal or overweight, did not correlate with discharge FIM.